INHIBITION OF HUMAN LOW-DENSITY LIPOPROTEINS OXIDATION BY Hibiscus radiatus CUV. CALYCES EXTRACT - Hernawan Hernawan (Indonesian Journal of Chemistry, 2008)
Hibiscus radiatus Cuv calyces extracts rich in polyphenols was screened for their potential to inhibit oxidation of human low-density lipoproteins-cholesterol (LDL-C) in vitro. The inhibition of LDL-C oxidation (antioxidant activity) was determined by measuring the formation of conjugated dienes and thiobarbituric acid reagent substances (TBARS). LDL-C oxidation was carried out in the presence of H. radiatus Cuv calyces extract (20 and 50 μM). CuSO4 (10 μM) was used as the oxidation initiator and  butylated hydroxytoluene (BHT) at 50 μM was used as standard antioxidant. The protective effect of H. radiatus Cuv. calyces extract toward human low-density lipoproteins, complex lipid system was  demonstrated by significant increase lag time (> 103 min), diminished of the propagation rate (44 %), and diminution of conjugated dienes formation 59.42 % (50 μM) compared to control.